Prawo właściwe dla czynności prawnych związanych z zarządem sukcesyjnym - Górecki, Jacek (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The Act of 5 July 2018 on the succession administration of the business of a physical person introduced a possibility to carry out transactions relating to establishing and performing administration of the estate. In particular, the Act permits to appoint a succession administrator and empowers him or her to carry out legal transactions relating to the business of the deceased entrepreneur. A need to determine the law applicable to these legal transactions arises. The article contains an analysis of the conflict rules adopted in the EU Succession Regulation. From this analysis the author draws a conclusion that the appointment of the succession administrator and the legal acts relating thereto are subject to the law applicable to succession. Likewise one should classify legal transactions relating to the administration of the business undertaken by persons named in the Act to carry out administration in the period before the succession administration is established. The prerequisites of the validity of the legal transactions carried out by the effectively nominated succession administrator on the other hand are subject to the law applicable to the given legal transactions, as according to general rules relating thereto. This includes, inter alia, that the legal acts falling with the scope of the law applicable to succession (Article 23 of the Succession Regulation), are governed by that law.